Photosensitization and mechanism of cytotoxicity induced by the use of ALA derivatives in photodynamic therapy - Casas, A. (2001)
The use of more lipophilic derivatives of 5-aminolevulinic acid (ALA) is expected to have better diffusing properties, and after conversion into the parent ALA, to reach a higher protoporphyrin IX (PPIX) formation rate, thus improving the efficacy of topical photodynamic therapy (PDT). Here we have analysed the behaviour of 3 ALA derivatives (ALA methyl-ester, hexyl ester and a 2-sided derivative) regarding PPIX formation, efficiency in photosensitizing cells and mechanism of cellular death. The maximum amount of porphyrins synthesized from 0.6 mM ALA was 47 ± 8 ng/105 cells. The same amount was formed by a concentration 60-fold lower of hexyl-ALA and 2-fold higher of methyl-ALA. The 2-sided derivative failed to produce PPIX accumulation. Applying a 0.6 J cm-2 light dose, cell viability decreased to 50%. With the 1.5 J cm-2 light dose, less than 20% of the cells survive, and higher light doses produced nearly total cell killing. Comparing the PPIX production and the induced phototoxicity, the more the amount of porphyrins, the greater the cellular killing, and PPIX formed from either ALA or ALA-esters equally sensitize the cells to photoinactivation. ALA-PDT treated cells exhibited features of apoptosis, independently on the pro-photosensitizer employed. ALA-PDT can be improved with the use of ALA derivatives, reducing the amount of ALA necessary to induce efficient photosensitization. © 2001 Cancer Research Campaign.